THE EXEMPLARY CHARACTER OF PROPHET MUHAMMAD AS A POSITIVE ROLE MODEL FOR ADOLESCENTS IN THE VIRTUAL ERA - Laura Paramita; Mahmud Al Chusairi. ME (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The digital era has fundamentally changed how teenagers interact and form their character. This research aims to analyze the relevance of Prophet Muhammad's exemplary character as a positive character reference for teenagers in the virtual era. Using qualitative research methods with a library research approach, this study examines various literature related to Prophet Muhammad's exemplary character, Islamic character education, and challenges faced by teenagers in the digital era. The research results show that the four main characteristics of Prophet Muhammad, namely siddiq, amanah, tabligh, and fathonah, have very significant relevance in the digital context. The siddiq trait provides a foundation for healthy digital literacy, amanah teaches responsibility in technology use, tabligh provides guidance for positive communication, and fathonah encourages wise use of technology. The main challenges faced by teenagers include digital identity crisis, online social pressure, technology addiction, and excessive information exposure. The implementation model developed includes a character education framework based on exemplary behavior, mentoring programs with a sunnah approach, and integration of Islamic values in digital literacy curriculum. Practical implementation is carried out through developing Islamic netiquette, information verification techniques based on tabayyun principles, and forming positive communities on digital platforms. This research contributes to the development of character education strategies that are appropriate to the challenges of the digital era.